Socio-Anthropologie Du Processus D’autonomisation Des Femmes Rurales Ivoiriennes À Travers Les Activités Génératrices De Revenus - Youl Félix; Kouame Aya Lydie-Marcelle; Kouakou Aya Larissa; Toh Alain (European Scientific Journal, ESJ, 2017)
This article focuses on the rationale behind women's choices of economic activities in the Gomon Sub-Prefecture and the methods used to implement these activities. Specifically, it describes the strategies used by the women of the Gomon Sub-prefecture to ensure their financial autonomy and provides insights into the difficulties behind syndicating these women. Using both qualitative and quantitative assessment tools, this study targeted women involved in income-generating activities in the sub-prefecture. To overcome poverty, women have invested in the production, processing and marketing of food. The decision-making process described in this article demonstrates that these women make rational choices in the daily management of their income-generating activities aimed specifically at maximizing the economic gains necessary to their financial autonomy and the improvement of their social status.